42 Multi-agent allergies as predictor of functional neurological disorder. (28th May 2019) - Zarkali, Angeliki; Edwards, Mark; Yogarajah, Mahinda
Abstract : Objectives/Aims: Functional neurological disorders (FND) account for 20% of patients in neurology clinics and can lead to functional impairment, multiple re-attendances and significant cost. However, diagnosing FND remains challenging; identifying associated factors could aid earlier diagnosis. We aimed to determine the value of self-reported multi-allergies as predictor for FND. Methods: We retrospectively reviewed records of consecutive patients from two clinics (General Neurology and FND), St George's Hospital, January 2015–June 2018. A logistic regression model was used in conditional fashion; statistically significant variables in univariate analysis were included. Results: Of 720 patients with definitive diagnosis, 243 (33.8%) had FND and 477 (66.3%) another neurological disorder. Mean age was 43 years (range 16–93), 63.9% (453) were female. 81 patients with FND (33%) had Non-epileptic attack disorder (NEAD). In multivariate analysis, factors associated with FND were female sex (Odds Ratio [95% Confidence Intervals], OR=0.49 [0.33, 0.73], p<0.001), psychiatric comorbidity (OR=4.28 [2.89, 6.35], p<0.001), younger age (OR=0.97 [0.96, 0.98], p<0.001), coexisting fibromyalgia/chronic fatigue syndrome (OR=4.85 [1.26, 18.73], p=0.02) and allergies (OR=2.54 [1.79, 3.62], p<0.001). Polypharmacy, medical comorbidities, atopy and hypermobility were not significant. Increased number of allergies increased the probability of FND: one allergy OR=4.53 [3.08, 6.65, p<0.001], two OR=9.09 [3.92, 21.09, p<0.001], three OR=16.74 [3.82, 73.43, p<0.001] and ≥4 allergies OR=42.94 [2.51, 736.02, p=0.009]. Conclusions: Previous studies highlighted the increased prevalence of allergies in NEAD compared to epilepsy. Our study expand this to all FND, as only 1 in 3 FND patients had NEAD. Presence of allergies, particularly to multiple agents, should raise the suspicion of FND.